Stable Transfection of Eimeria intestinalis and Investigation of Its Life Cycle, Reproduction and Immunogenicity - Shi, Tuanyuan; Tao, Geru; Bao, Guolian; Suo, Jingxia; Hao, Lili; Fu, Yuan; Suo, Xun (Frontiers in Microbiology, 2016)
Rabbit coccidiosis, caused by infection of Eimeria spp. is one of the most severe parasitic diseases in rabbits. E. intestinalis is one of the most immunogenic species in rabbit coccidia. Due to the lack of genomic information and unsuccessful in vitro cultivation, genetic manipulation of rabbit coccidia lagged behind other apicomplexan parasites. Using regulatory sequences from E. tenella, we obtained a transgenic line of E. intestinalis expressing yellow fluorescent protein (YFP). YFP was continuously expressed throughout the whole life cycle. Morphological features of E. intestinalis in the different developmental stages were dynamically observed with the transgenic line. Some important features in the endogenous development stages were observed. Trophozoites were found as early as 4 h post inoculation. Two-types of schizonts and merozoites were observed in first three of the four schizogonies. Beside jejunum and ileum, gametogony stage and oocysts were also found in the duodenum and vermiform appendix. In addition, the transgenic strain was highly immunogenic but less pathogenic than the wild type. Considering the high immunogenicity of E. intestinalis and amenability to transfection with foreign genes, transgenic E. intestinalis could be a promising oral eukaryotic vaccine vector.